Efektivitas permainan tradisional bakiak terhadap keterampilan sosial pada siswa sekolah dasar MI NW al-mujahidin tahun 2024 - Pipin Taria; Elya Wibawa Syarifoeddin; Supriadin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The problem in this research is the minimal use of Physical Education, Sports, and Health (PJOK) learning that utilizes traditional games to develop children's social skills. This study aims to determine the effectiveness of the traditional game Bakiak on the social skill levels of elementary school students at MI NW Al-Mujahidin in 2024. This type of research is descriptive. The method used is descriptive qualitative, with data collection techniques utilizing observation sheets. The population in this study consisted of 20 fourth-grade students at MI NW Al-Mujahidin in 2024, selected using a total sampling technique. Data analysis involved descriptive analysis presented in the form of percentages. Based on the average score of 30, the effectiveness of the traditional game Bakiak on the social skills of children at MI NW Al-Mujahidin in 2024 is in the